Study the Levels of Glucagon Like Peptide-1(GLP-1) and Related Parameters in Iraqi Hyperlipidemia Patients with Diabetes Mellitus. - A. Lazim, Ahmed; A. Lafta, Muntaha (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The glucagon-like peptide-1 is secreted by intestinal L cells in response to nutrient ingestion. It regulates the secretion and sensitivity of insulin while suppressing glucagon secretion and decreasing postprandial glucose levels , additionally, glucagon-like peptide-1 delays gastric emptying and suppresses appetite. The impaired secretion of glucagon-like peptide-1 has negative influence on hyperlipidemia, diabetes  and insulin resistance related diseases the levels of its secretion change with the intake of different nutrients. Some drugs also have influence on GLP-1 secretion .